FHL1 as a prognostic biomarker and therapeutic target in acute promyelocytic leukaemia - Bo Luo; Wei Li; Jingyuan Zeng; Yingyu Mao; Shuang He; Nan Hu; Qulian Guo; Xiaoli Zheng (Discover Oncology)
Abstract Acute myeloid leukemia (AML) has a poor prognosis and high heterogeneity. Most cases of leukemias are caused by environmental factors interacting with the cell’s genetic material, but treatment is still dominated by cell cycle drugs. Therefore, there is an urgent need to find reliable biomarkers. Based on the Gene Expression Omnibus database, Kaplan–Meier survival analysis and univariate Cox regression analysis were used to select the genes that had the most significant influence on the prognosis of patients with AML. Quantitative real-time PCR and Western blot were used to assess the effects of small interfering RNA transfection and lentiviral interference on the gene's knockout and overexpression, respectively. These method were also used to confirm the expression levels of the FHL1 gene in the HL60 cell line compared to neutrophils.. Cell Counting Kit-8 and flow cytometry were used to detect the effect of high or low expression of FHL1 on cell viability and apoptosis under the influence of cytarabine and daunorubicin. FHL1 was found to be the most prognostic independent biomarker by GSE12417 screening and GSE37642 validation. FHL1 is highly expressed in AML, and knockdown of FHL1 can increase the sensitivity of AML cells to cytarabine and daunorubicin. FHL1 may play a role as a potential molecular marker and therapeutic target for predicting poor prognosis of AML and for direct treatment (chemotherapy).